Perspectives of medical students on future work‐life balance in Japan: A qualitative study using postlecture comments. (12th September 2022) - Matsui, Tomoko; Inoue, Machiko
Abstract: Background: Recently, work‐life balance (WLB) has grown in popularity among medical professionals, and an increasing number of institutions are including WLB lectures into medical school curricula. In Japan, medical student lectures concerning WLB were given in at least 50% of universities. However, with these changes in social awareness, it is not fully clear how current medical students view WLB. The purpose of this study is to explore how Japanese medical students think about their future WLB from the perspective of constructivism. Method: We used one of the present authors' work career and life cycle as an example of a physician's career in a lecture for medical students on community medicine in 2020. Students were asked to remark on their thoughts on the talk and their views on future WLB, and we analyzed their comments qualitatively to understand the current male and female medical students' perspectives on future WLB. Result: We used the feedback of 119 participants (71 males and 48 females). Most students, regardless of gender, thought WLB was essential, but the factors they mentioned as being connected to WLB mirrored the continuing traditional notions of gender‐based division of labor and doctors' fixed‐job image. Male students' views, on the other hand, were more varied, reflecting recent generational shifts. Conclusions: For the improved WLB in medical doctors, it would be required to tackle the problem from several angles, including not just increasing support for WLB but also fostering an awareness of the essence of WLB in pregraduate medical school. Abstract : This study qualitatively explored how Japanese medical students think about their future work‐life balance (WLB) using post‐lecture comments, from the perspective of constructivism. For the improvement of WLB among doctors, the necessity of fostering awareness of the nature of WLB in medical school before graduation was shown.